Preparation method of ceramsite with efficient ammonia nitrogen adsorption and microorganism loading functions
By optimizing the raw material formula and sintering process of the ceramic granules, high-strength lightweight ceramic granules with high-efficiency ammonia nitrogen adsorption and microbial loading functions were prepared, which solved the problem of insufficient performance of commercial ceramic granules and achieved more efficient ammonia nitrogen adsorption and microbial loading effects.
Patent Information
- Application Number
- CN202411912852.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
AI Technical Summary
Commercially available ceramic particles generally have problems such as large apparent density, small specific surface area, low porosity and poor ammonia nitrogen adsorption performance, which is difficult to meet the needs of MBBR nitrogen removal process.
By optimizing the raw material formula and sintering process of the ceramic granules, high-strength light ceramic granules with high-efficiency ammonia nitrogen adsorption and microbial loading functions are prepared. The specific steps include mixing the chemical components of the bottom sludge, zeolite, and bentonite, sintering at a specific temperature after granulation, and adjusting the sintering parameters to improve the specific surface area and porosity of the ceramic.
The prepared functional ceratops have a high specific surface area and porosity, which significantly improves the ammonia nitrogen adsorption capacity and microbial load capacity. The apparent density is close to the density of water, and the fluidization performance is good, which meets the standards of high-strength light ceratops.
Smart Images

Figure CN119874401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste utilization, and in particular to a method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions. Background Art
[0002] Suspended fillers are the core part of the MBBR process. They provide suitable growth and reproduction conditions for microbial attachment, directly affect the structure, performance and morphology of the biofilm, and ultimately determine the performance of the reactor in removing pollutants. Commonly used polyhedral hollow spheres and cylindrical suspended fillers made of polypropylene and polyethylene are rigid fillers with high porosity, good strength, toughness and stability. They can be processed into various shapes, with an apparent density close to that of water and excellent hydraulic properties. However, there are also some defects: such as poor hydrophilicity and bioaffinity of fillers, difficulty in microbial biofilm formation, easy detachment of biofilm on fillers, lack of microporous structure, unsatisfactory biological microenvironment, and lack of adsorption capacity for ammonia nitrogen pollutants. Suspended carriers made of polyurethane and polyester, such as sponges and synthetic fiber balls, are more hydrophilic than polypropylene and polyethylene materials. At the same time, the porous structure of the carrier provides a protective place for microorganisms, reduces the influence of hydraulic shear and friction between carriers on microbial growth in the initial biofilm formation, thereby accelerating microbial attachment. However, due to the soft structure, the pore structure is unstable, and problems such as blockage and agglomeration are prone to occur during wastewater treatment. In view of the limitations of plastic materials, researchers have carried out physical and chemical modification on the surface of different fillers with the goal of enhancing biocompatibility, material stability and harmlessness, and have achieved certain results. However, most modified materials are currently expensive and are far from reaching the level of large-scale production and market application.
[0003] Lightweight ceramsite is cheap and easy to obtain. It has a rough surface and rich pore structure inside. It can form more stable aerobic zones and anoxic / anaerobic zones in different parts of the ceramsite, providing a stable microenvironment for the simultaneous nitrification and denitrification process of the entire reactor. It is very suitable as a substitute for MBBR plastic fillers. At present, the main raw materials for preparing ceramsite for water treatment in my country are clay and shale, which account for 50% and 33% of the raw materials of ceramsite respectively. The use of solid wastes such as fly ash, domestic sludge, and riverbed mud as raw materials to prepare ceramsite only accounts for a small part, which does not meet the requirements of sustainable development. Dredging sludge is rich in SiO 2 、Al 2 O 3 The alkaline earth metal components are similar to the properties of shale and clay. Without adding or with a small amount of auxiliary raw materials, ceramsite with good performance can be fired through appropriate processes. According to statistics, the amount of sediment brought by dredging in the Bohai Sea, Yangtze River Delta and Pearl River Delta in my country is 1 billion m3 per year. 3If such a large amount of dredged sediment is not properly handled, it will not only occupy a large amount of land resources but also cause secondary pollution to the surrounding environment. Using dredged sediment to prepare ceramsite for water treatment is a new way to achieve "waste treatment with waste". Ceramsite prepared from solid waste such as sediment is widely used in aerated biological filter, infiltration tank and artificial wetland and other water treatment fields, and has achieved good results in removing organic pollutants, heavy metals and TP, but it also generally has a large apparent density (1.28-1.75g / cm 3 ), small specific surface area (1 to 5 m 2 / g), low porosity (30-50%) and poor ammonia nitrogen adsorption performance. As the core component of MBBR denitrification process, it is necessary to start with the raw material formula design and sintering process of ceramsite to prepare high-strength and lightweight ceramsite with ammonia nitrogen adsorption and nitrification and denitrification microbial carrier functions. Summary of the invention
[0004] In view of the problems that the currently available ceramsite on the market generally has, such as large apparent density, small specific surface area, low porosity and poor ammonia nitrogen adsorption performance, the present invention provides a method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions, starting from the raw material formula design and sintering process of ceramsite, to prepare high-strength and lightweight ceramsite with ammonia nitrogen adsorption and nitrification and denitrification microbial carrier functions.
[0005] The technical solution of the present invention is: a method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions, comprising the following steps:
[0006] S1. Based on the chemical composition of the sediment, zeolite and bentonite, the sediment, zeolite and bentonite are selected in a ratio of 35-45%:35-45%:10-30% by mass, the sediment, zeolite and bentonite are ground through a 100-mesh sieve, and stirred and mixed for 3-8 minutes to obtain a mixed material;
[0007] S2, granulating the mixed material in a granulator, spraying deionized water at a solid-liquid ratio of 1g:0.1-0.3ml during the granulation process to obtain a spherical ceramic blank;
[0008] S3, drying the spherical ceramic blank, and then firing it in a muffle furnace, pre-firing it at 300-450°C for 5-20min, then uniformly heating it to 1000-1150°C at a heating rate of 15-25°C / min, sintering it at 1000-1150°C for 4-10min, and cooling it to room temperature with the furnace to obtain functional ceramsite.
[0009] Description: The preheating of spherical ceramic blanks is to remove residual moisture, prevent cracking due to rapid temperature changes, and adjust the chemical composition of the balls to achieve the best burning expansion effect; by uniformly heating the balls at a heating rate of 15 to 25 ° C / min, heating the balls to a preset sintering temperature, and maintaining the corresponding sintering time, high-strength and lightweight ceramsite with the function of ammonia nitrogen adsorption and nitrification and denitrification microbial carrier can be prepared.
[0010] Furthermore, by adjusting the proportions of different raw materials, each component in the mixed powder can meet the composition requirements of the swellable ceramsite. 2 The mass ratio of Al is 48-78%, 2 O 3 The mass ratio of SiO is 10-25%, the mass ratio of flux is 13-26%, and the mass ratio of SiO 2 +Al 2 O 3 / flux = 3.5 to 10, wherein the flux is Fe 2 O 3 , CaO, MgO, Na 2 O.K 2 The sum of O.
[0011] Note: From the analysis of the chemical composition of the raw materials, the flux component in the dredging sludge is relatively low, which will make the ceramsite roasting temperature high and the viscosity of the liquid phase high, which is not conducive to the expansion of the ceramsite; and from the composition of clinoptilolite, its SiO 2 and Al 2 O 3 The content is much higher than that of dredged sludge, so zeolite can be used as a regulator in the sintering formula of expanded clay to make up for the deficiency of Si and Al in the sludge components, thereby improving the mechanical strength of the fired expanded clay.
[0012] In addition, the alkaline oxides of bentonite (Fe 2 O 3 +CaO+MgO+Na 2 O+K 2 O) content is relatively high, reaching 26.70%. Using bentonite as a binder and flux to fire expanded clay can make up for the deficiency of alkaline oxides in dredged sludge, reduce the sintering temperature, promote the formation of molten liquid phase, and improve the expansion performance of expanded clay. In addition, the ignition loss of the sludge sample is relatively high, indicating that its organic matter content is relatively large, which is conducive to the generation of gas during the sintering process and promotes the expansion of expanded clay.
[0013] Furthermore, the particle size of the spherical ceramic blank is 10 mm.
[0014] Note: If the diameter of the ball is too small, sintering is likely to occur, and if it is too large, it is difficult to burn through. Therefore, the diameter of the spherical pottery blank should be 10mm.
[0015] Furthermore, the method for drying the spherical ceramic blank is: drying at 100-110° C. for 3-6 hours.
[0016] Note: By drying at the above temperature for 3 to 6 hours, the quality of the spherical ceramic blank can be stabilized, providing stable spherical ceramic blanks for subsequent sintering processes.
[0017] Furthermore, the moisture content of the spherical ceramic blank is controlled at 8-24%.
[0018] Note: Since the bentonite in the ingredients has strong water absorption properties, the greater the amount added, the more water is required in the granulation process. Through repeated experiments and explorations, it was found that when the moisture content of the ball is between 8% and 24%, the spherical ceramic blank is easy to form and no powder falls off.
[0019] Furthermore, the temperature of the deionized water is 10-50°C.
[0020] Note: At a lower water temperature for spray granulation, the evaporation rate of droplets is slower, which may lead to larger differences between droplets, making the distribution of particles wider. At a higher water temperature, the evaporation rate of droplets is faster, the radius of droplets is reduced, and the distribution of particles becomes more concentrated. However, at a lower water temperature, the pore structure may be open and loose, while at a higher water temperature, the pore structure may become tighter and more closed. Therefore, the temperature of deionized water has a certain influence on the performance of expanded clay. By using the above-mentioned deionized water temperature for spray granulation, expanded clay with better and more stable performance can be obtained.
[0021] Furthermore, deionized water is divided into low-temperature deionized water and high-temperature deionized water according to room temperature. During the granulation process in the granulator, low-temperature deionized water and high-temperature deionized water are sprayed alternately;
[0022] The single spraying volume of low-temperature deionized water accounts for 5-8% of the total amount of deionized water, and the single spraying volume of high-temperature deionized water accounts for 2-5% of the total amount of deionized water.
[0023] Note: Changes in the temperature of deionized water will affect the interaction forces between particles, including van der Waals forces, electrostatic forces and capillary forces. The balance of these forces determines the degree of agglomeration and stability of the particles. Too high or too low water temperatures may lead to an imbalance in the forces between the particles, thereby affecting the agglomeration effect of the particles. On this basis, by using alternating low-temperature deionized water and high-temperature deionized water for spray granulation, the distribution of expanded clay can be more concentrated, and functional expanded clay with good specific surface area and porosity can be obtained.
[0024] Furthermore, during the low-temperature deionized water spraying, ultrasonic treatment with an ultrasonic power of 50 to 80 W and a frequency of 20 to 30 KHz is added.
[0025] Note: By using the auxiliary treatment of the above-mentioned ultrasonic parameters, problems such as uneven particle shape, wide particle size distribution range and large difference in particle quality can be avoided, thereby improving the granulation effect of expanded clay, making the particle shape and size more controllable, and obtaining functional expanded clay with better performance.
[0026] The beneficial effects of the present invention are:
[0027] 1) The present invention optimizes the optimal raw material ratio and sintering parameters for preparing functional ceramsite, so that the physical and chemical properties of the ceramsite meet the process requirements of being a biofilm carrier of a moving bed biofilm reactor (MBBR). The optimized functional ceramsite has a higher specific surface area and porosity, overcomes the shortcomings of commercially available ceramsite, such as serious enamelization on the surface, low open porosity, and lack of ammonia nitrogen adsorption function. The heavy metal leaching concentration is lower than the national standard, and the ceramsite can be safely used in the field of water treatment.
[0028] 2) The specific surface area and porosity of the functional ceramsite of the present invention can reach up to 53.41m 2 / g and 56.76%, which are 31.79 times and 1.32 times of commercially available ceramsite. It has large ammonia nitrogen adsorption capacity, rough surface, strong microbial loading capacity, apparent density close to the density of water, good fluidization performance, and compressive strength in line with the high-strength light coarse aggregate standard of density grade 600 in "Light Aggregate and Its Test Method" (GB / T17431.2-2010). The large specific surface area and porosity of functional ceramsite are very conducive to the adsorption of ammonia nitrogen pollutants in wastewater and the biofilm of microorganisms; and the apparent density of functional ceramsite is closer to the density of water than commercially available ceramsite, which is conducive to its suspension in MBBR, with low fluidization energy consumption, and is more suitable as a suspension carrier for moving bed biofilm reactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a process flow chart for the preparation of functional expanded clay. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.
[0031] Example 1: A method for preparing ceramsite with high efficiency ammonia nitrogen adsorption and microbial loading function, such as Figure 1 As shown, the following steps are included:
[0032] S1. Based on the chemical compositions of the sediment, zeolite and bentonite, the sediment, zeolite and bentonite are selected in a ratio of 40%:40%:20% by mass; the sediment, zeolite and bentonite are ground through a 100-mesh sieve, stirred and mixed for 5 minutes to obtain a mixed material;
[0033] Specifically, the main chemical components of the sediment, zeolite and bentonite were determined, as shown in Table 1:
[0034] Table 1 Chemical composition of raw materials (%)
[0035]
[0036] Among them, SiO 2 The mass ratio of Al is 51.28%, 2 O 3 The mass ratio of SiO is 12.71%, the mass ratio of flux is 15.14%, and 2 +Al 2 O 3 / solvent=4.23, the flux is Fe 2 O 3 , CaO, MgO, Na 2 O.K 2 The sum of O; calculated as follows:
[0037] Ceramsite SiO 2 Mass ratio = 40.73*40% + 63.20*40% + 48.55*20% = 51.28;
[0038] Ceramic Al 2 O 3 Mass ratio = 8.23*40% + 16.51*40% + 14.02*20% = 12.71;
[0039] Ceramic fluxing component (Fe 2 O 3 +CaO+MgO+Na 2 O+K 2 O) mass ratio = (6.24 + 3.13 + 2.19 + 0.61 + 2.13) * 40% + (4.21 + 1.62 + 1.91 + 0.78 + 1.69) * 40% + (7.14 + 10.42 + 4.30 + 2.62 + 2.22) * 20% = 15.14;
[0040] SiO 2 +Al 2 O 3 / (Fe 2 O 3 +RO+R 2O)=(51.28+12.7) / 15.14=4.23;
[0041] S2, granulating the mixed material in a granulator, spraying deionized water in a solid-liquid ratio of 1g:0.2ml during the granulation process, to obtain spherical ceramic blanks with a particle size of 10mm, wherein the water content of the spherical ceramic blanks is controlled at 16%;
[0042] S3, the spherical ceramic blank is dried at 105°C for 6h, then calcined in a muffle furnace, pre-calcined at 350°C for 10min, then uniformly heated to 1100°C at a heating rate of 20°C / min, sintered at 1100°C for 6min, the power of the muffle furnace is turned off, and the ceramic blank is cooled to room temperature with the furnace to obtain functional ceramsite.
[0043] In order to verify the use effect of the functional ceramsite of the present invention, the functional ceramsite and the commercially available ceramsite were tested for relevant performance indicators according to the methods specified in "Artificial ceramsite filter material for water treatment" and "Light aggregate and its test method" and compared with the national standard;
[0044] 1) Experimental methods
[0045] The functional ceramsite prepared in Example 1 was used to remove ammonia nitrogen from wastewater. The specific steps of the adsorption experiment were as follows: 2.5 g of functional ceramsite was weighed and put into a 500 mL stoppered conical flask, and 10 mg / L of NH 4 + -N simulated wastewater 250mL was shaken at 120r / min for 8h in a 20℃ environment, and the supernatant was taken and filtered through a 0.22μm filter membrane to analyze and determine NH 4 + -N equilibrium concentration;
[0046] The functional ceramsite is used for microbial loading. The specific steps of the loading experiment are as follows: a 500mL stoppered glass conical flask is used to construct a ceramsite microbial loading function evaluation device, which is equipped with an aeration system. The weighed ceramsite is placed in the conical flask, and 250mL of the composite bacterial solution is added. After continuous cultivation for 7 days, the amount of fixed microorganisms on the ceramsite is determined to evaluate the proliferation of microorganisms on the ceramsite. Among them, the amount of fixed microorganisms on the ceramsite is determined by weighing method, characterized by the volatile solid concentration per unit weight of ceramsite, and the result is expressed in mg VS / (g carrier). Take an appropriate amount of ceramsite and put it into an evaporating dish of known weight, dry it to constant weight at 105℃, and the weight increased by deducting the weight of the evaporating dish is the total solid amount. The evaporating dish is moved into a muffle furnace at 550℃ again for high temperature ashing to constant weight, and the weight reduced is the volatile solid amount (VolatileSolid, VS). The volatile solid mass divided by the total solid mass is the volatile solid concentration.
[0047] VS=m1 -m 2 Formula 1
[0048]
[0049] Where: m 0 is the weight of the evaporating dish, in g; m 1 The weight of ceramsite and evaporating dish after drying at 105℃, in g; m 2 It is the weight of ceramsite and evaporating dish after high temperature ashing at 550℃, in g.
[0050] 2) Experimental results
[0051] Example 1 Specific surface area and porosity of functional ceramsite, the results are shown in Table 2 below:
[0052] Table 2 Specific surface area and porosity of functional ceramsite
[0053]
[0054] The results show that the specific surface area and porosity of the functional ceramsite in Example 1 reached 53.41 m 2 / g and 56.76%. The specific surface area of functional ceramsite mainly depends on the microporous structure in the ceramsite. Zeolite, as a layered aluminosilicate mineral, has a rich mesoporous structure. This is the main reason why the specific surface area of fired ceramsite increases significantly with the increase of zeolite content. The porosity of ceramsite is closely related to its expansion performance. The dredged sludge contains a large amount of organic matter, which is the main source of gas-producing substances in ceramsite embryo balls and the main reason for the expansion of ceramsite with a certain viscosity. The fluxing component (Fe 2 O 3 +CaO+MgO+Na 2 O+K 2 O) can be combined with SiO 2 and Al 2 O 3 Under lower temperature conditions, eutectic mixtures such as 4FeO·SiO are formed. 2 、2FeO·SiO 2 、Na 2 O·SiO 2 , K 2 O·SiO 2 、4FeSiO 3 +CaO·SiO 3 Increasing the proportion of bentonite in the ball within a certain range can help to melt SiO 2 and Al 2 O 3 The effect of skeleton components such as argon and argon can make the sintered ceramsite produce enough liquid phase and suitable viscosity at a lower temperature, which effectively promotes the expansion of ceramsite.
[0055] In the MBBR process, the larger specific surface area and porosity of functional ceramsite are very beneficial to the adsorption of ammonia nitrogen pollutants in wastewater and the biofilm formation of microorganisms. The apparent density of functional ceramsite is closer to the density of water than commercial ceramsite, which is beneficial for its suspension in MBBR. The compressive strength of functional ceramsite meets the high-strength light coarse aggregate standard of density grade 600 in "Light Aggregate and Its Test Methods" (GB / T17431.2-2010) (bucket density>0.5, ≤0.6g / cm 3 ; The compressive strength is greater than 4Mpa), which is sufficient to withstand the scouring of air and water flow and the collision and friction between particles during the operation of MBBR, and has a long service life. The ammonia nitrogen adsorption capacity of functional ceramsite is 0.87mg / g, the removal efficiency of ammonium ions in wastewater is 87%, and the bioload is 12.73mg VS / (g carrier). Functional ceramsite has high ammonia nitrogen adsorption efficiency and microbial loading performance. On the one hand, this is because the addition of zeolite increases the specific gravity of the internal mesoporous structure of functional ceramsite, increases the sites for ceramsite to adsorb ammonia nitrogen, and gives it selective adsorption of ammonia nitrogen. On the other hand, because functional ceramsite has a pore structure that is connected inside and outside, microorganisms can pass through open pores and be loaded in the pores on the inner surface of ceramsite.
[0056] 3) Experimental comparison
[0057] Comparative Example 1 and Comparative Example 2 are provided. Both Comparative Example 1 and Comparative Example 2 are commercially available ceramsites. The physical and chemical properties of the functional ceramsite of this embodiment and the commercially available ceramsite of Comparative Examples 1 and 2, as well as the ammonia nitrogen removal rate, adsorption capacity and bioload are tested and compared, respectively. The results are shown in Table 3 and Table 4 below:
[0058] Table 3 Physical and chemical properties of ceramsite
[0059]
[0060]
[0061] Note: a refers to "Artificial ceramsite filter material for water treatment" (CJ / T299-2008)
[0062] Table 4 Comparison of ammonia nitrogen removal rate, adsorption capacity and bioload of functional ceramsite and commercial ceramsite
[0063]
[0064] The results show that the specific surface area and porosity of commercial ceramsite are significantly smaller than those of functional ceramsite. Although the compressive strength of commercial ceramsite is greater than that of functional ceramsite, its bulk density is high, which is not conducive to its suspension in MBBR, and the fluidization energy consumption is large. In addition, commercial ceramsite basically does not have the ability to adsorb ammonia nitrogen. Its removal rate for ammonia nitrogen wastewater is only 2.3% at most, and its maximum ammonia nitrogen adsorption capacity is only 0.023 mg / g. The adsorption of ammonia nitrogen by commercial ceramsite may only come from the physical adsorption on the surface of ceramsite. The internal pores of commercial ceramsite are small, mainly mesopores. As the microorganisms grow, these pores are easily blocked, resulting in the obstruction of the transmission of oxygen and nutrients required for microbial growth and a decrease in biomass. It can be seen that the surface immobilization and proliferation efficiency of microorganisms are closely related to the pore structure of ceramsite. Functional ceramsite with a rough surface, an open pore structure and an appropriate proportion of macropores has a stronger microbial loading function. Compared with commercial ceramsite, functional ceramsite is more suitable as a suspension carrier for moving bed biofilm reactors.
[0065] At the same time, comparative example 3 was set up, and the raw materials and preparation steps of its high-strength lightweight ceramsite were the same as those of Example 1, except that in this embodiment, the ammonium ion concentration in the solution was measured after 4 hours of oscillation during the adsorption experiment. In the microbial load test, the microbial load was measured after 3 days of continuous cultivation. The results are shown in Table 5 below:
[0066] Table 5 Comparison of ammonia nitrogen removal rate, adsorption capacity and bioload of functional ceramsite
[0067]
[0068] The results show that, like Example 1, the ammonia nitrogen adsorption capacity of Comparative Example 3 is 0.82 mg / g in the 4-hour adsorption experiment, and the removal efficiency of ammonium ions can still reach 82%. After 3 days of proliferation, the bioload is 8.87 mg VS / (g carrier), indicating that the functional ceramsite can achieve rapid adsorption of ammonia nitrogen and rapid biofilm formation of microorganisms.
[0069] Example 2: The difference between this example and Example 1 is that the mass percentages of the bottom mud, zeolite and bentonite in this example are 35%:35%:30%; wherein the SiO 2 The mass ratio of Al is 50.94%, 2 O 3 The mass ratio of SiO is 12.87%, the mass ratio of flux is 16.59%, and 2 +Al 2 O 3 / Solubilizer = 3.85.
[0070] Example 3: This example is different from Example 1 in that the mass percentages of the bottom mud, zeolite, and bentonite in this example are 45%:45%:10%; wherein the SiO 2 The mass ratio of Al is 51.62%, 2 O 3 The mass ratio of SiO is 12.54%, the mass ratio of flux is 13.70%, and 2 +Al 2 O 3 / Solubilizer = 4.68.
[0071] Example 4: This example is different from Example 1 in that deionized water is sprayed in a solid-liquid ratio of 1g:0.1ml during the granulation process, and the moisture content of the spherical ceramic blank is controlled at 8%.
[0072] Example 5: This example is different from Example 1 in that deionized water is sprayed in a solid-liquid ratio of 1g:0.3ml during the granulation process, and the moisture content of the spherical ceramic blank is controlled at 24%.
[0073] Example 6: This example is different from Example 1 in that the spherical ceramic blank is dried at 100° C. for 6 hours.
[0074] Example 7: This example is different from Example 1 in that the spherical ceramic blank is dried at 110° C. for 3 h.
[0075] Example 8: This example is different from Example 1 in that the steel is pre-fired at 300°C for 5 minutes, then the temperature is uniformly increased to 1000°C at a heating rate of 15°C / min, and sintered at 1000°C for 4 minutes.
[0076] Example 9: This example is different from Example 1 in that the steel is pre-fired at 450°C for 20 min, then the temperature is uniformly increased to 1150°C at a heating rate of 25°C / min, and sintered at 1150°C for 10 min.
[0077] Example 10: This example is different from Example 1 in that the temperature of the deionized water is 34°C.
[0078] Example 11: This example is different from Example 10 in that the temperature of the deionized water is 10°C.
[0079] Example 12: This example is different from Example 10 in that the temperature of the deionized water is 50°C.
[0080] Embodiment 13: This embodiment is different from Embodiment 10 in that the deionized water is divided into low-temperature deionized water and high-temperature deionized water according to the room temperature (25°C). Specifically, the low-temperature deionized water is 15°C and the high-temperature deionized water is 34°C. During the granulation process in the granulator, the low-temperature deionized water and the high-temperature deionized water are sprayed alternately.
[0081] Among them, the single spraying volume of low-temperature deionized water accounts for 6% of the total amount of deionized water, and the single spraying volume of high-temperature deionized water accounts for 4% of the total amount of deionized water.
[0082] Example 14: This example differs from Example 13 in that the single spraying amount of low-temperature deionized water accounts for 8% of the total amount of deionized water, and the single spraying amount of high-temperature deionized water accounts for 2% of the total amount of deionized water.
[0083] Example 15: This example differs from Example 13 in that the single spraying amount of low-temperature deionized water accounts for 5% of the total amount of deionized water, and the single spraying amount of high-temperature deionized water accounts for 5% of the total amount of deionized water.
[0084] Example 16: This example differs from Example 13 in that, during the low-temperature deionized water spraying, an ultrasonic treatment with an ultrasonic power of 70w and a frequency of 25KHz is added.
[0085] Example 17: The difference between this example and Example 16 is that ultrasonic treatment with an auxiliary ultrasonic power of 50w and a frequency of 20KHz is added.
[0086] Example 18: The difference between this example and Example 16 is that ultrasonic treatment with an auxiliary ultrasonic power of 80w and a frequency of 30KHz is added.
[0087] In order to verify the influence of various process parameters and methods of the functional ceramsite of the present invention on the use effect of the functional ceramsite, the ammonia nitrogen removal rate, adsorption capacity and bioload of the functional ceramsite prepared in each embodiment were tested and compared by the above experimental method. The results are shown in Table 6 below:
[0088] Table 6 Comparison of ammonia nitrogen removal rate, adsorption capacity and bioload of functional ceramsite
[0089]
[0090]
[0091]
[0092] The results show that the use of different process parameters and methods has a certain impact on the effect of functional ceramsite, but the effect of functional ceramsite is significantly better than that of commercially available ceramsite. The analysis is as follows:
[0093] 1) The influence of different raw material ratios on the use effect of functional ceramsite
[0094] By comparing Example 2 and Example 3 with Example 1, it can be seen that the use effect of the functional ceramsite prepared by using different mass ratios of sludge, zeolite and bentonite has a certain influence. On the basis of Example 1, making the addition ratio of sludge and zeolite smaller or larger affects the expansion and microporous structure of the ceramsite, resulting in a decrease in its specific surface area and porosity, and causing its ammonia nitrogen adsorption capacity and microbial load to decrease. Therefore, the mass ratio of sludge, zeolite and bentonite in Example 1 is relatively optimal.
[0095] 2) Effect of different spherical ceramic moisture content on the use effect of functional ceramsite
[0096] By comparing Example 4 and Example 5 with Example 1, it can be seen that the subsequent drying and sintering using different spherical ceramic blanks has a certain influence on the use effect of the prepared functional ceramsite. On the basis of Example 1, increasing or decreasing the moisture content of the spherical ceramic blank affects the expansion and microporous structure of the ceramsite, resulting in a decrease in its specific surface area and porosity, resulting in a decrease in its ammonia nitrogen adsorption capacity and microbial load. Therefore, the moisture content of the spherical ceramic blank in Example 1 is relatively optimal.
[0097] 3) Effect of different spherical ceramic drying parameters on the use of functional ceramsite
[0098] By comparing Example 6 and Example 7 with Example 1, it can be seen that the use of different spherical ceramic blank drying parameters has a certain influence on the use effect of the prepared functional ceramsite. On the basis of Example 1, lowering or increasing the drying temperature and time will cause its ammonia nitrogen adsorption capacity and microbial load to decrease, but the decrease in Example 6 is not obvious. This may be because the synergistic effect of Example 1 on this basis is not significant. Therefore, the functional ceramsite prepared in Example 1 is relatively optimal, but it can be adjusted as needed according to the actual production situation with reference to the data of Example 6.
[0099] 4) Effect of different sintering process parameters on the use of functional ceramsite
[0100] By comparing Example 8 and Example 9 with Example 1, it can be seen that the use of different sintering process parameters has a certain influence on the use effect of the prepared functional ceramsite. The addition ratio of raw materials in Example 8 and Example 9 relative to Example 1 remains unchanged, but the sintering temperature becomes smaller / increased and the sintering time becomes shorter / longer. The sintering temperature and sintering have a great influence on the specific surface area and porosity of the ceramsite. When the sintering temperature is too high or the sintering time is too long, the amount of liquid phase on the surface of the ceramsite increases and the viscosity decreases. These liquid phases will fill into the pores, causing the porosity and specific surface area of the ceramsite to decrease. Therefore, the functional ceramsite prepared in Example 1 is relatively optimal.
[0101] 5) Effect of different granulation spraying deionized water temperatures on the use of functional ceramsite
[0102] By comparing Example 10 with Example 1, it can be seen that Example 1 uses 25°C room temperature deionized water, and after spraying granulation with deionized water at different temperatures, the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite have changed to a certain extent compared with Example 1; it can be seen that the deionized water granulation spraying at different temperatures has a certain influence on the performance of ceramsite;
[0103] At the same time, through the comparison of Example 11, Example 12 and Example 10, it can be seen that after spraying granulation with deionized water containing different temperatures, there is a certain influence on the use effect of the prepared functional ceramsite, among which the functional ceramsite prepared in Example 10 is relatively optimal.
[0104] 6) The influence of different granulation processes on the use effect of functional ceramsite
[0105] By comparing Example 13 with Example 10, it can be seen that the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite can be further improved by using the granulation process of Example 13. It can be seen that by controlling the spraying temperature of deionized water by the method of Example 13, the spherical ceramic blank forms a uniform particle internal structure with a higher specific surface area and porosity.
[0106] At the same time, through the comparison of Example 14, Example 15 and Example 13, it can be seen that the parameters of different granulation processes have some influence on the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite. On the basis of Example 13, the temperature and cooling rate of the granulation process are adjusted, so that the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite are reduced to a certain extent. Therefore, the functional ceramsite prepared in Example 13 is relatively optimal.
[0107] 7) The influence of different granulation processes on the use effect of functional ceramsite
[0108] By comparing Example 16 with Example 13, it can be seen that the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite can be further improved after using ultrasound-assisted low-temperature deionized water spraying. It can be seen that by adopting the method of Example 16, high-strength and lightweight ceramsite with better performance can be obtained;
[0109] At the same time, through the comparison of Example 17, Example 18 and Example 16, it can be seen that the use of different ultrasonic parameters has some influence on the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite. The ultrasonic parameters are adjusted on the basis of Example 16, so that the ammonia nitrogen removal rate, adsorption capacity and bioload of the prepared functional ceramsite are reduced to a certain extent. Therefore, the functional ceramsite prepared in Example 16 is relatively optimal.
Claims
1. A method for preparing ceramsite with high efficiency ammonia nitrogen adsorption and microbial loading function, characterized in that: The following steps are involved: S1. Based on the chemical composition of the sediment, zeolite and bentonite, the sediment, zeolite and bentonite are selected in a ratio of 35-45%:35-45%:10-30% by mass, the sediment, zeolite and bentonite are ground through a 100-mesh sieve, and stirred and mixed for 3-8 minutes to obtain a mixed material; S2, granulating the mixed material in a granulator, spraying deionized water at a solid-liquid ratio of 1g:0.1-0.3ml during the granulation process to obtain a spherical ceramic blank; S3, drying the spherical ceramic blank, and then firing it in a muffle furnace, pre-firing it at 300-450°C for 5-20min, then uniformly heating it to 1000-1150°C at a heating rate of 15-25°C / min, sintering it at 1000-1150°C for 4-10min, and cooling it to room temperature with the furnace to obtain functional ceramsite.
2. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions according to claim 1, characterized in that: The mass proportion of SiO2 in the mixed powder is 48-78%, the mass proportion of Al2O3 is 10-25%, the mass proportion of flux is 13-26%, and SiO2+Al2O3 / solvent=3.5-10, wherein the flux is the sum of Fe2O3, CaO, MgO, Na2O, and K2O.
3. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions according to claim 1, characterized in that: The particle size of the spherical ceramic blank is 10 mm.
4. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading function as claimed in claim 1, characterized in that: The method for drying the spherical ceramic blank is: drying at 100-110° C. for 3-6 hours.
5. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions as claimed in claim 1, characterized in that: During the granulation process, deionized water is sprayed at a solid-liquid ratio of 1g:0.1-0.3ml, and the water content of the spherical ceramic blank is controlled at 8-24%.
6. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions according to claim 1, characterized in that: The temperature of the deionized water is 10-50°C.
7. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions as claimed in claim 6, characterized in that: Deionized water is divided into low-temperature deionized water and high-temperature deionized water according to room temperature. During the granulation process in the granulator, the low-temperature deionized water and the high-temperature deionized water are sprayed alternately. The single spraying volume of low-temperature deionized water accounts for 5-8% of the total amount of deionized water, and the single spraying volume of high-temperature deionized water accounts for 2-5% of the total amount of deionized water.
8. The method for preparing ceramsite with high-efficiency ammonia nitrogen adsorption and microbial loading functions as claimed in claim 7, characterized in that: During the low-temperature deionized water spraying, ultrasonic treatment with an ultrasonic power of 50 to 80 W and a frequency of 20 to 30 KHz is added.